Pengaruh Penggunaan Media Power Point Interaktif (Pointer), Media Gambar Dan Motivasi Belajar Terhadap Hasil Belajar: The Effect of Using Interactive PowerPoint Media (with Pointer), Image-Based Media, and Learning Motivation on Learning Outcomes - Christanto, Benny; Rusmawati, Retno Danu; Wiyarno, Yoso (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Low learning outcomes and student motivation in science and social studies (IPAs) at the elementary school level, often attributed to the limited use of interactive learning media, represent a critical issue that warrants investigation. This study aimed to examine the effects of using interactive PowerPoint (pointer), image-based media, and learning motivation on students’ learning outcomes, as well as to test the hypothesis of an interaction between media type and motivation. The subjects of this study were 53 third-grade students of SDN Inpres Nabarua, divided into an experimental group using a pointer and a control group using image-based media, employing a 2×2 factorial experimental design; data were collected through validated and reliable learning outcome tests and motivation questionnaires, and analyzed using two-way ANOVA after testing for normality and homogeneity. The results indicate that both learning media and motivation significantly affect students’ learning outcomes, with pointer media being more effective than image-based media, particularly for students with high motivation. Additionally, there is a significant interaction between media and motivation in determining learning outcomes. These findings emphasize that the effectiveness of learning media strongly depends on student motivation, suggesting that optimal I-PA learning strategies require a synergy between interactive media and efforts to enhance student motivation, thereby achieving better academic performance.